PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA INSTRINSIK, DAN MOTIVASI KERJA EKSTRINSIK TERHADAP KINERJA PEGAWAI PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN PANDEGLANG - Tubagus Regiasa (Jurnal Bina Bangsa Ekonomika, 2023)
This study aims to determine the Effect of Transformational Leadership, Intrinsic Work Motivation, and Extrinsic Work Motivation on Employee Performance at the Regional Development Planning Agency of Pandeglang Regency with Job Satisfaction as Intervening. In this study examined five variables, namely three independent variables (exogenous), one dependent variable (endogenous) and one intervening variable. The independent variables are transformational leadership, intrinsic work motivation, and extrinsic work motivation. While the dependent variables are employee performance and intervening variable satisfaction. This research was carried out at the Regional Development Planning Agency of Pandeglang Regency by sampling using saturated sampling techniques  , totaling 97 respondents. Primary data was collected using a questionnaire in the form of a list of statements accompanied by open-ended questions, then the data was analyzed using SEM (structural equation model) techniques  using the help of SmartPLS software. The first hypothesis that states that transformational leadership has a positive and significant effect  on job satisfaction is supported or accepted, meaning that the higher the application of transformational leadership, the job satisfaction of employees (subordinates) will increase.  The second hypothesis that states intrinsic motivation has a positive effect is not significant  on job satisfaction, meaning that intrinsic motivation possessed by employees has a positive influence on employee job satisfaction, but not significantly.  The third hypothesis that extrinsic motivation has a positive and significant effect  on job satisfaction is rejected, meaning that extrinsic motivation has no impact on employee job satisfaction.  The fourth hypothesis that transformational leadership has a positive and significant effect on  employee performance is rejected, meaning that the application of transformational leadership has no impact on improving employee performance.  The fifth hypothesis that  states that  intrinsic motivation has a positive and significant effect  on employee performance is rejected, meaning that the intrinsic motivation possessed by employees has not been able to improve employee performance. The sixth hypothesis that extrinsic motivation has a positive and significant  effect on employee performance is rejected, meaning that extrinsic motivation has no effect on employee performance.  The seventh hypothesis states that  job satisfaction has a positive and significant effect  on employee performance is supported or accepted, meaning that the higher the level of employee job satisfaction, the employee performance will increase